خدمات ما بعد البيع في تحسين صورة العلامة التجارية لدى الزبائن –دراسة عينة لزبائن مؤسسة اتصالات الجزائر -وحدة سوق أهراس- - إيمان قداش; علي بارة (My University, 2022)
This study aimed to show the correlation and influence between after-sales services and brand image. It contained two parts, the first part dealt with the theoretical aspect in which the variables of the study were dissected, after-sales services as an independent variable, and the image of the brand as a dependent variable, while the second part was devoted to the field study that took place in Algeria Telecom, Souk-Ahras unit. Where the students relied mainly on distributing a questionnaire to a sample of 100 individuals, and 74 forms were retrieved capable of statistical analysis, with a response rate of 74%. After the analysis process that was relied on the statistical program SPSS, this study came to the following: - There is a clear perception among the respondents about the after-sales services and the image of the brand in the institution under study. - The study showed that there is a positive correlation between after-sales services and brand image, and the most important relationship was between maintenance and repair service and brand image. - The study also showed that there is an effect between after-sales services and the image of the brand, and the most important influence relationship was between the maintenance and repair service and the image of the brand. ................................................ هدفت هذه الدراسة إلى تبيان علاقة الارتباط والتأثير بين خدمات ما بعد البيع وصورة العلامة التجارية. وقد احتوت هذه الدراسة على جزئين، الجزء الأول تناول الجانب النظري الذي تم فيه تشريح متغيرات الدراسة، خدمات ما بعد البيع كمتغير مستقل، وصورة العلامة التجارية كمتغير تابع، أما الجزء الثاني فقد خصص للدراسة الميدانية التي تمت في مؤسسة اتصالات الجزائر وحدة سوق أهراس. حيث اعتمد الطلبة بشكل أساسي على توزيع إستبانة على عينة مكونة من 100 فرد، وتم استرجاع 74 استمارة قابلة للتحليل .% الإحصائي بنسبة استجابة قدرت ب 74 توصلت هذه الدراسة إلى: spss بعد عملية التحليل التي تم الاعتماد فيها على البرنامج الإحصائي - هناك تصور واضح لدى المبحوثين حول خدمات ما بعد البيع وصورة العلامة التجارية في المؤسسة قيد الدراسة. - أظهرت الدراسة أن هناك علاقة ارتباط موجبة بين خدمات ما بعد البيع وصورة العلامة التجارية، وكانت أهم علاقة بين خدمة الصيانة والتصليح وصورة العلامة التجارية. - كما أظهرت الدراسة أن هناك تأثير بين خدمات ما بعد البيع وصورة العلامة التجارية، وكانت أهم علاقة تأثير بين خدمة الصيانة والتصليح وصورة العلامة التجارية.